Alcohol ablation of atrioventricular conduction. Issue 3 (March 1991) - Sneddon, J F; Ward, D E; Simpson, I A; Linker, N J; Wainwright, R J; Camm, A J
Abstract : Transcoronary ablation of atrioventricular conduction by dehydrated alcohol was attempted in 14 patients with refractory atrial arrhythmias. Alcohol (0.5 or 1.0 ml) was delivered after selective catheterisation of the atrioventricular nodal artery in the 10 patients in whom the artery could be identified by cineangiography. The other four patients underwent electrical ablation when the nodal artery could not be catheterised. Temporary atrioventricular block induced by dilute contrast and cold saline (0.9%) confirmed that the catheter was in the correct position before the alcohol was delivered. In all 10 patients complete atrioventricular block developed after alcohol ablation. The block persisted in all four patients given 1.0 ml alcohol but not in four of the six given 0.5 ml. The mean (SD) creatine kinase (MB fraction) at four to six hours after ablation was 76.5 (49.5) IU after 1.0 ml and 75.5 (43.1) IU after 0.5 ml alcohol (normal less than 20 IU). The overall success rate of alcohol ablation in the whole group on an "intention to treat" basis was 43%. The procedure was a technical success in six of the 10 patients in whom the nodal artery was identified. Transcoronary alcohol ablation of atrioventricular conduction should be considered in patients in whom electrical techniques have been unsuccessful.